Analysis of the Impact of the Work Environment Toward Employee Work Motivation at PT. XYZ - Inna Hanarti; Minggu; Dwi Okti Utami; Hakim; Eka Travilta Oktaria; Supadi Bambang Sutrisno (MANAGER: Journal of Management and Administration Science, 2024)
This study was conducted to analyse the impact of the work environment on employee motivation at PT. XYZ. The purpose of this research is to identify obstacles and alternative solutions to problem-solving. Data collection techniques include observation, by directly observing the research object, and field documentation techniques to obtain essential information regarding the analysis of the impact of the work environment on employee motivation at PT. XYZ. Based on the discussion, the results indicate that the analysis of the impact of the work environment on employee motivation at PT. XYZ is already quite good. Employees and leaders share a strong sense of family, as many employees come from the leader's family and the local community. However, there are some challenges, such as suboptimal room temperature, insufficient office facilities, workplace layout, and the need for renovation of damaged buildings. The suggested solutions include improving work facilities, organizing the workspace, and renovating office buildings.